Effect of Several physicochemical treatments on seed apricot germination cultivar "Kalabi": Effect of some physicochemical treatments on the germination of apricot seeds, cultivar "Kalabi" - مخول جرجس (Latakia University Journal -Biological Sciences Series, 2025)
The research was conducted in Tishreen university nursery, and Agriculture Engineering Faculty, to study the effect both priming and soaking with gibberellic acid solution, to remove apricot seed dormancy. The results showed that seed soaking with GA3 (500ppm) for 24 hours, followed by stratification for 90 days, gave significant higher germination rate (91.67%), followed by 90 days stratification (83.33%), while the control showed a lower germination rate (8.33%). Statistical analysis showed that stratification for 90 days and soaking with GA3 (500 ppm) for 24 hours, were significantly better compared to the other treatments. The germination speed of seeds stratified for 120 days before and after soaking with 500ppm GA3 solution for 24 hours was 7.59 – 7.32 – 8.56 and 7.54 days/seed, while control seed germination was slower (140.69 days/seed).